(untitled) - Cresswell, Helen (Đồng Nai, 2009)
'Moondial!' As Minty spoke the word, a cold wind went past her, and her ears were filled with a thousand frightened voices. She shut her eyes and put her hands over her ears - and the voices and the wind went away. Minty opened her eyes ...and knew that she was in a different morning, not the one she had woken up to. And so Minty's strange adventure begins - a journey through time into the past, where she finds Tom, and Sarah... and the evil Miss Vole.
Keywords: English language,England literature,Ngôn ngữ tiếng Anh,Phiêu lưu mạo hiểm; Readers,Người thích đọc sách